Assessing spiritual well-being: relating with God explains greatest variance in spiritual well-being among Australian youth - Fisher, John W. (International journal of children's spirituality, 2013)
How do we set standards in assessing spiritual well-being (SWB)? Most measures provide only scores on arbitrary scales. Therefore, if the questions differ, the scores are likely to as well. This paper reports on two scales developed with 460 Australian secondary school students, with diverse cultural and religious backgrounds, from state, Catholic, Christian Community and independent schools. The four domains model of spiritual health/well-being was the theoretical base from which 12 items were developed to reflect quality of relationships with each of self, others, environment and God/the Divine. The instrument with the five top-scoring items in each domain, known as Spiritual Health And Life-Orientation Measure (SHALOM), has been sought for use in over 200 studies in 20 languages. The second-highest sets of five items were extracted and found to form statistically valid factors, for a new instrument called SWBQ2. As would be expected, the mean values for the factor scores varied between SHALOM and SWBQ2, overall and by school type. However, regression analyses of the lived experience scores showed that relating with God provided greatest explanation of variance in SWB, on both measures. A double-response method introduced for SHALOM was also used with SWBQ2 to compare each person’s lived experience with their ideals, better reflecting quality of relationships, rather than just the arbitrary scores. There was negligible difference in dissonance scores on the four factors in both measures, that is, in comparing the difference between ideals and lived experiences. This method showed consistency in the quality of relationships reflecting SWB, contrasted with variance shown using only lived experience, as mentioned above. Relating with God was again most influential on SWB. These findings have implications for methods used in assessing SWB as well as outcomes.